A case study of the generation of angular momentum and angular velocity in somersault backward stretched with 2/1 and 3/1 twists performed by a single varsity male gymnast - Harigai, R.; Ae, M.; Ae, K.; Seo, K.; Hatakeda, Y.; Arii, S. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to compare the angular momentum and angular velocity in somersault backward stretched with different number of twists performed by a single varsity male gymnast. The 3D motion captured system (Qualisys, 250Hz) was used to collect kinematic data of a single varsity male gymnast A who performed the somersault backward stretched with a double (2/1) and a triple (3/1) twist. The angular momenta and angular velocities of the body segments and whole body were calculated by the Tang`s method. More than a half of the twist angular momentum of the whole body in both 2/1 and 3/1 twists was generated during the take-off phase, which indicated that the gymnast A was classified as a contact twist type. In case of the gymnast A there seemed no difference in angular momenta of 2/1 and 3/1 twists, although he generated the angular momentum of the twist earlier in 3/1 than 2/1. He controlled the number of twists by his body maneuver before landing. Since these findings were obtained from a single gymnast, we need to investigate twist techniques and angular momentum date of various gymnasts.